Facile biocatalytic synthesis of a macrocyclic lactone in sub- and supercritical solvents. (March 2014) - Karmee, Sanjib Kumar; Niemeijer, Bernd; Casiraghi, Laura; Mlambo, Benhilda; Lapkin, Alexei; Greiner, Lasse
Abstract High yield and selectivity in the intramolecular synthesis of the macrocyclic lactone oxacyclohexadecan-2-one were achieved via a straightforward biocatalytic synthesis utilising non-conventional solvents: supercritical carbon dioxide (scCO2), ethane, fluoroform and 1, 1, 1, 2-tetrafluoroethane. Batch and continuous syntheses were demonstrated with a higher yield attained in a continuous synthesis using in-situ product extraction by scCO2. A remarkably high yield was obtained in 1, 1, 1, 2-tetrafluoroethane at batch conditions.